Developing global competitiveness by assessing organized retail productivity using data envelopment analysis - Reeti Agarwal; Ankit Mehrotra (International Journal of Business Science & Applied Management (IJBSAM), 2009)
The purpose of this paper was to find out (using Regression, Data Envelopment Analysis and Sensitivity Analysis) how efficiently some of the top organized India retail companies have been performing relative to each other over the years and thereby to identify factors that help increase the efficiency of a retail company. The study was conducted based on the analysis of data downloaded from Prowess database for five Indian retail companies for the time period 2000-2007. The paper is deemed to be helpful to enable Indian retail companies gain a competitive advantage in the face of increased competition being faced in the emerging organized retail sector in India. The findings brought forth Advertising and Marketing expenses as the significant performance determining factors to be paid attention to.
Keywords: 650; global competitive advantage; organized retail; data envelopment analysis (DEA); performance determinants; performance indicators